2018
DOI: 10.3390/ijms19041216
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Expression Analysis of the Hsf Family, and Characterization of Class A4 in Sedum Alfredii Hance under Cadmium Stress

Abstract: Sedum alfredii Hance, a cadmium (Cd)/zinc (Zn)/lead (Pb) co-hyperaccumulating species, is a promising phytoremediation candidate because it accumulates substantial amounts of heavy metal ions without showing any obvious signs of poisoning. The heat shock transcription factor (Hsf) family plays crucial roles in plant growth, development, and stress responses. Although the roles of some Hsfs in abiotic stress have been well studied in model plants, the Hsf family has not been systematically investigated in heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 55 publications
4
18
0
Order By: Relevance
“…Activities of SOD, APX and CAT in transgenic chrysanthemum overexpressing CmHsfA4, were higher than those of WT lines under salt stress . In addition, Hsf activates the expression of downstream genes (including Hsps) and shows a similar pattern of expression to protect plants from external stress (Snyman and Cronjé, 2008;Xue et al, 2014;Xue et al, 2015;Chen et al, 2018). In the present study, we also observed that transgenic Arabidopsis and NHE S. alfredii expressing SaHsfA4c showed higher CAT, POD, and APX activities than those of the WT after Cd stress, and were able to induce the expression of ROS-scavenging system related genes (POD, CAT and APX) and Hsps.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Activities of SOD, APX and CAT in transgenic chrysanthemum overexpressing CmHsfA4, were higher than those of WT lines under salt stress . In addition, Hsf activates the expression of downstream genes (including Hsps) and shows a similar pattern of expression to protect plants from external stress (Snyman and Cronjé, 2008;Xue et al, 2014;Xue et al, 2015;Chen et al, 2018). In the present study, we also observed that transgenic Arabidopsis and NHE S. alfredii expressing SaHsfA4c showed higher CAT, POD, and APX activities than those of the WT after Cd stress, and were able to induce the expression of ROS-scavenging system related genes (POD, CAT and APX) and Hsps.…”
Section: Discussionsupporting
confidence: 77%
“…We previously observed that 18 SaHsfs showed a high expression level among the 22 members of the Hsf gene family identified in hyperaccumulation ecotype (HE) S. alfredii after Cd treatment. Furthermore, SaHsfA4c improves the Cd tolerance and accumulation in transgenic yeast (Chen et al, 2018). The function of SaHsfA4c in the regulation of Cd tolerance, however, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed 78 HSFs in wheat (Zhou et al, 2019), 35 in carrot (Huang et al, 2015), and 25 in tea (Zhang et al, 2020c). Based on the relationship between protein sequence, structure, and evolution, there are three types of members in the HSF family in plants: A, B, and C. All types of HSFs in various plants have great similarity (Zhu et al, 2017b;Chen et al, 2018). HSF in class A is mainly responsible for the regulation of heat shock gene expression; while HSF in class B has DNA-binding activity but has no heat shock-induced transcriptional activation activity, which may be a coregulator or inhibitor of genes in class A, and the functions of HSF in class C are unclear (Hu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The OrthoMCL algorithm (Li et al 2003) (Finn et al 2011) was conducted to identify and screen for possible SaGELPs containing Lipase_GDSL (Pfam: PF00657) domains in S. alfredii (Chen et al 2018). The GELP homologous sequences in A. thaliana were obtained from TAIR (https://www.arabidopsis.org/index.jsp).…”
Section: Identification Of Sagelps In S Alfredii Hancementioning
confidence: 99%
“…Quantitative Real-Time PCR (qRT-PCR) reactions were carried out using the SYBR ® Green premix Ex Taq TM (TaKaRa) reagent on the thermal circulator of an Applied Biosystems 7300 Real-Time PCR System (Applied Biosystems, Foster City, CA, USA) (Chen et al 2018). Sequences of primers used in qRT-PCR are shown in Table S1.…”
Section: Total Rna Isolation and Expression Analysismentioning
confidence: 99%